Die Klimate der Erde.: Eine Klassifikation auf ökophysiologischer Grundlage der realen Vegetation - Lauer, Wilhelm; Rafiqpoor, M. Daud; Frankenberg, Peter (ERDKUNDE, 1996)
In this contribution a classification of climates of the earth is presented on the base of eco-physiological characteristics of the real vegetation. It considers the regional differentiation of the heat and water budget as well as the interaction of the system climate-soil-plant in the sense of an ecological circuit . The delimitation of climatic zones is based on the spatial variation of solar radiation. The limits of the four principal zones (tropics, subtropics, mid-latitudes and polar regions) are quantitatively marked by day-length variation of irradiation. Within the solar radiation zones, climatic types are defined on the base of parameters of the he at and water budget. These climatic types form spatial units (climatic regions) by the interference of the isolines indicating the duration of the thermic (Isothermomenes) and hygric (Isohygromenes) vegetation period. The duration of the thermic vegetation period is defined by the number of months with average temperatures above a certain threshold-value. They mark the beginning and the end of the vegetative phase. The duration of hygric vegetation period results in the water budget equation: N - pLV. A month, however, is humid when the precipitation reaches at least the calculated potential landscape evapotranspiration (pLV). The climatic map, developed with the aid of the hygrothermic parameter, shows the present state of the climatic configuration of the earth’s surface, including its actual cover of plant. The methodical way opens up the possibility to record quantitatively every climatic variation caused by a change of vegetation cover with the help of available data.